An economic analysis of continuous positive airway pressure for the treatment of obstructive sleep apnea-hypopnea syndrome. - Weatherly, H; Griffin, S; Mc Daid, C; Durée, K; Davies, R; Stradling, JR; Westwood, M; Sculpher, M (2009)
OBJECTIVES: An important option for the medical treatment of obstructive sleep apnea-hypopnea syndrome (OSAHS) is continuous positive airway pressure (CPAP) during sleep. This study reports on the cost-effectiveness of CPAP compared with dental devices and lifestyle advice. The work was commissioned by the NHS HTA Programme to inform the National Institute of Health and Clinical Excellence's (NICE) appraisal of CPAP. METHODS: A Markov model compared the interventions over the expected patient lifetime. The primary measure of cost-effectiveness was the incremental cost per quality-adjusted life-year (QALY) gained. The QALY incorporated the impact of treatments on daytime sleepiness, blood pressure and health-related quality of life (HRQoL). RESULTS: On average, CPAP was associated with higher costs and QALYs compared with dental devices or lifestyle advice. In the base-case analysis, the incremental cost-effectiveness ratio (ICER) for CPAP compared with dental devices was around 4,000 pounds per QALY (2005--06 prices). The probability that CPAP is more cost-effective than dental devices or lifestyle advice at a threshold value of 20,000 pounds per QALY was 0.78 for men and 0.80 for women. Several sensitivity analyses were undertaken and it was found that the ICER for CPAP consistently fell below 20,000 pounds per QALY gained, apart from in a subgroup with mild disease. CONCLUSIONS: The model suggests that CPAP is cost-effective compared with dental devices and lifestyle advice for adults with moderate or severe symptomatic OSAHS at the cost-effectiveness thresholds used by NICE. This finding is reflected in the NICE guidance.